Further thoughts on promoting sustainable behavior change in physical activity settings - comment on Hohberg et al. - Nikos Ntoumanis (Bern Open Publishing, 2022)
In this commentary, I provide some reflections on the target article's discussion of the role of affect for physical activity promotion. I also offer further thoughts and suggestions on how to promote sustainable behavior change, addressing both conceptual and methodological issues.